Are nurses prepared to respond to next infectious disease outbreak: A narrative synthesis - Anliu Nie; Xiangfen Su; Mengyuan Dong; Wenjie Guan (Wiley, 2022)
Abstract Aim The review aimed to present a synthesis of nurses' preparedness for infectious disease and the components of emergency preparedness. Design Narrative synthesis. Methods A systematic search and screening for relevant studies were conducted to locate the relevant articles. The included studies were examined for scientific quality using the Mixed Methods Appraisal Tool. The findings of included studies were synthesized by a narrative synthesis approach. Results Totally 15 studies were included, and 4 themes associated with nurses' preparedness for pandemic were identified: knowledge and skills, psychological preparation, external resources, and attitude and intention. Conclusions Most nurses express a positive willingness to respond to epidemics, although they do not believe they are adequately prepared. Some measures should be taken for improving nurses' emergency preparedness, including providing ongoing training, protective equipment, safe working environment and psychological intervention, improving nurses' resilience and accelerating the sharing of scientific information about epidemics.